A reestruturação produtiva e a micro e pequena empresa brasileira: gestão da qualidade, estrutura flexível, retorno financeiro e a vida social dos empresários - Oliveira, Marco Antonio Gonsales de (2010)
This study sought to draw in the context of productive restructuring and the role of micro and small enterprises in this context. Everything indicates that the small business is in a favorable environment for its development despite the employment crisis and the challenge of its own restructuring process in the administrative and technological low cost of small business. The small business is benefited by access to information technology, the flexible and lean toward the market demand and other features that have stimulated growth and stability of small business. In the first chapter there was a literature review on the restructuring, with national and international sources. It was discussed a few studies on the role of small business in the context of restructuring. The increasing participation of small business in the economy, outsourcing and networking, quality management and flexible structure were the themes. In the second chapter, through quantitative studies conducted by Dieese side and prepared by national Sebrae and São Paulo Sebrae, analyzed the reality of small business in Brazil in the restructuring process, from the opening of the domestic market in 1990. Mortality rates of small business of São Paulo and Brazil are in decline since 1997. There is growth in the number of small business, substantial increase in revenues and employment, besides the improvement in birth rate. However, stands the lowest salary of the employed and employees of small business in relation to medium and big companies. In the last chapter of this study, there were six interviews with the use of narrative voice recorder, micro and small entrepreneurs in São Paulo s industrial sector. The central themes such as quality management, structure and flexibility (outsourcing and networking), the financial return and the social life. We conclude that the small business are benefiting from restructuring of production by being part of the new production process of big companies and also of their own small business. The production model based on demand becomes more appropriate to the small business for its flexible and lean. According to research Sebrae, the financial return to owners of the small business is lower than that of the medium and big company, but the qualitative interviews of chapter three points to the financial satisfaction of most entrepreneurs. But with a high rate of dissatisfaction over social life. There were many complaints about the impossibility of taking a vacation, being with family, to have your schedule for recreation, among other activities outside the company